Emergency Scenario-Based Training Curriculum Development: Enhancement of Caregivers for the Elderly' Emergency Assistance Competency in a Rural Thai Community - Praditporn Pongtriang; Thassanee Soontorn; Jaruwat Sumleepun; Noawarat Chuson (SAGE Publishing, 2024)
Background Caregivers for the elderly are a critical component of the health care system, especially in rural communities. They play a crucial role, assisting older people in confronting emergency illnesses. Objective The study describes the process of developing an emergency scenario-based training curriculum (ESBTC) for caregivers of the elderly, focusing on geriatric life-threatening surveillance and emergency assistance (GLTSEA) in rural communities. Methods The descriptive qualitative research utilized for developing the ESBTC followed Karn's six steps of curriculum development: (1) needs assessment, (2) targeted needs assessment, (3) goals and objectives, (4) educational strategies, (5) implementation, and (6) evaluation and feedback. The research sample comprised community representatives engaged in providing care during emergency illnesses, emergency experts, and health care providers. A group discussion and focus group were conducted along with semi-structured interviews. The data were analyzed by content analysis following Creswell's six steps. Results The results revealed problems and needs related to the care and management of emergency illnesses in rural communities. Five main themes emerged, including insufficient knowledge, difficulties in communication, mindfulness and self-confidence, Unable to assess the initial symptoms, and a need for skills development. In the development step, the curriculum focused on skill development and continued follow-up to ensure necessary skills, such as providing basic life support, using automated external defibrillators, through training scenarios. In the evaluation step, the participants indicated that their emergency assistance skills had improved. The six main themes that emerged regarding the training continuity, courses, and competencies needed to support the emergency system for caregivers were benefits and value, competence enhancements, upstreaming confidence, sustainable development, challenges in curriculum development, and effective strategies. Conclusions The ESBTC combines community-based and realistic scenarios, involving the participation of community stakeholders. It is crucial to gather community feedback and needs assessments to formulate potential strategies as part of the curriculum.